1995
DOI: 10.1093/ajcn/61.5.1037
|View full text |Cite
|
Sign up to set email alerts
|

Feeding premature newborn infants palmitic acid in amounts and stereoisomeric position similar to that of human milk: effects on fat and mineral balance

Abstract: The effect of the structure of human milk triglycerides on intestinal fat absorption remains controversial. Twelve infants were each fed, for 1 wk in a crossover design, two formulas that differed only in triglyceride configuration. The "beta" formula contained triglycerides similar to those in human milk (26% palmitic acid, esterified predominantly to the sn-2 position) whereas in the "alpha" formula, which contained triglycerides similar to those in formulas currently marketed, palmitate was mainly at the sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
2
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 27 publications
4
112
2
5
Order By: Relevance
“…Similar results had been obtained in preterm infants (Carnielli et al, 1995) and rats (Aoyama et al, 1996;de Fown et al, 1994;Lien et al, 1993;Renaud et al, 1995;Tomarelli et al, 1968).…”
Section: Fatty Acid Composition Of Infant Formulassupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results had been obtained in preterm infants (Carnielli et al, 1995) and rats (Aoyama et al, 1996;de Fown et al, 1994;Lien et al, 1993;Renaud et al, 1995;Tomarelli et al, 1968).…”
Section: Fatty Acid Composition Of Infant Formulassupporting
confidence: 85%
“…Palmitic acid was also absorbed more with formulas rich in palmitic acid esterified at the sn-2 position of the triglycerides than with formulas containing palmitic acid largely esterified to the sn-1, 3 positions. These results were obtained in studies carried out on term infants (Carnielli et al, 1996;Filler et al, 1969), preterm infants (Carnielli et al, 1995) and rats (Aoyama et al, 1996;de Fown et al, 1994;Lien et al, 1993;Renaud et al, 1995;Tomarelli et al, 1968). Moreover, the location of palmitic acid in the sn-2 position in infant formulas improves the absorption of calcium in the small intestine (Lucas et al, 1997;Carnielli et al, 1996;Nelson et al, 1996).…”
Section: Introductionmentioning
confidence: 86%
“…Carnielli et al (1994) recently evaluated the effects of two formulas for preterm infants, differing only in the isomeric position of palmitic acid, on the absorption of fat and fatty acids and on mineral balance in a crossover study in preterm infants. The palmitic acid content of both formulas was 25-26% of total fatty acids.…”
Section: S T R U C T U R E D L I P I D Smentioning
confidence: 99%
“…However, these two studies showed that a high degree of palmitic acid in the sn-2 position of dietary triglycerides resulted in a significant decrease in faecal calcium excretion as calcium soaps (Carnielli et al, 1995;Lucas et al, 1997).…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 97%
“…Three of the studies (Carnielli et al, 1995(Carnielli et al, , 1996Lucas et al, 1997) used calcium balance methods and included measures of calcium absorption, whereas one study (Kennedy et al, 1999) assessed the effects of beta-palmitate on BMD and BMC. Carnielli et al (1995) conducted a randomised, double-blind, controlled, cross-over intervention study to address the effects of beta-palmitate on fat and mineral balance in 12 healthy preterm infants (birth weight 1.4±0.2 kg, weight during study period 2.1±0.3 kg, postnatal age 38±7 days). The intervention and control formulae only differed in the percentage of palmitic acid in the sn-2 position of dietary triglycerides (58 % in the intervention "beta" formula versus 9.8 % in the control formula without beta-palmitate) and were administered for one week each with no washout period.…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%